PUBLIC ORGANIZATIONS IN THE TRANSFORMATION OF UKRAINE'S PUBLISHING SECTOR - Shyrokova, Iryna (Sworld-Us Conference proceedings, 2025)
This study explores the role of public organizations in the transformation processes of Ukraine’s publishing sector under conditions of martial law and economic instability. The activities of leading civil society institutions are analyzed, including the